Research on Heat Dissipation Effect of Radiator Structure of Disc Brake for High-speed Train - Xin WANG; Guoquan WANG; Yong CHEN (机车电传动)
In order to improve the safety of the braking process of high-speed train, the brake disc heat dissipation structure needs to be optimized. The ANSYS-workbench software was used to establish a three-dimensional transient model. The temperature field simulation was performed on the brake discs with 8 different structural parameters based on the energy folding algorithm. The initial friction braking condition was obtained when the initial braking speed was 350 km/h. The change mechanism of the temperature field and the thermal stress field of the brake disc was analyzed by changing the height, the arrangement density and the discharge angle of the radiator. The simulation found that increasing the drainage angle, height of the heat dissipation ribs, and reducing the arrangement density can contribute to the heat dissipation of the brake disc; in the emergency braking project, the highest temperature point is on the brake disc surface, and the maximum thermal stress is on the side of the heat dissipation rib; In all 8 schemes, scheme 7 meets the braking requirements of high-speed trains with the initial speed of 350 km/h, the highest temperature is the lowest in all schemes, and the maximum thermal stress is reduced by 36 MPa.